2021
DOI: 10.36982/jiegmk.v12i2.1305
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penganggaran Partisipatif Dan Asimetri Informasi Terhadap Budgetary Slack Dengan Moral Equity Sebagai Variabel Moderasi

Abstract: <div class="WordSection1"><p><em>Research on the effect of participatory budgeting and information asymmetry on budgetary slack still shows the inconsistency of conflicting results. This study aims to provide empirical evidence about the effect of participatory budgeting and information asymmetry on the tendency to make budgetary slack and the effect of moral equity as a moderating variable on the relationship between the variables of participatory budgeting, information asymmetry, and budget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…Especially in providing accurate information in accordance with the actual circumstances in order to assist in the decision-making process so that the budget target can be achieved in accordance with the alignment of organizational goals. This research is in line with research conducted by Rahim et al (2013) and Iriansyah et al (2021) the result that there is a positive significant effect of budget participation on the tendency to create budgetary slack.…”
Section: G the Role Of Participatory Budgeting In Moderating The Effe...supporting
confidence: 92%
“…Especially in providing accurate information in accordance with the actual circumstances in order to assist in the decision-making process so that the budget target can be achieved in accordance with the alignment of organizational goals. This research is in line with research conducted by Rahim et al (2013) and Iriansyah et al (2021) the result that there is a positive significant effect of budget participation on the tendency to create budgetary slack.…”
Section: G the Role Of Participatory Budgeting In Moderating The Effe...supporting
confidence: 92%
“…H4 : Job relevant information berpengaruh negatif terhadap budgetary slack (Huseno, 2018;Iriansyah et al, 2021;Sarwendhi, 2021;Tyas et al, 2021;Yulaikah et al, 2021) H5 : Job relevant information dapat memoderasi pengaruh partisipasi penyusunan anggaran terhadap kinerja manajerial (Faizal et al, 2021;Firman et al, 2022;Rokhman & Pribadi, 2018) H6 : Job relevant information dapat memoderasi pengaruh partisipasi penyusunan anggaran terhadap budgetary slack (Huseno, 2018;Yulaikah et al, 2021)…”
Section: 1unclassified
“…Berdasarkan hasil penelitian terdahulu yang menyebutkan bahwa asimetri informasi berpengaruh negatif signifikan terhadap budgetary slack (Iriansyah et al, 2021). Begitu juga dengan hasil penelitian lain yang menyimpulkan bahwa ajob relevant information berpengaruh negatif tetapi tidak signifikan terhadap budgetary slack (Zulaika, 2022).…”
Section: Pengaruh Job Relevant Information Terhadap Budgetary Slackunclassified
See 1 more Smart Citation
“…The behavioral aspect in budget preparation reflects positive behavior because it can motivate managers to improve their performance and conversely it can also give rise to negative behavior such as internal conflict and budget gaps (Iriansyah et al, 2021). Research conducted by Apriwandi et al, (2013) concluded that manager participation in budget preparation will have a positive effect on the manager's performance, the higher the participation in budget preparation, the better the performance will be.…”
Section: Introductionmentioning
confidence: 99%